Cheer Choice - Jake Maddox (Stone Arch Books, 2014)
Colleen is devastated when her best friend changes schools--but when she learns that Meredith is teaching her new cheerleading squad the routine they created together for an upcoming competition their friendship is tested.
Keywords: Sport Stories -- Sport Stories